Bait attending fishes of the abyssal zone and hadal boundary: Community structure, functional groups and species distribution in the Kermadec, New Hebrides and Mariana trenches. (March 2017) - Linley, T.D.; Stewart, A.L.; McMillan, P.J.; Clark, M.R.; Gerringer, M.E.; Drazen, J.C.; Fujii, T.; Jamieson, A.J.
Abstract: Baited landers were deployed at 83 stations at four locations in the west Pacific Ocean from bathyal to hadal depths: The Kermadec Trench, the New Hebrides Trench, the adjoining South Fiji Basin and the Mariana Trench. Forty-seven putative fish species were observed. Distinct fish faunal groups were identified based on maximum numbers and percentage of observations. Both analyses broadly agreed on the community structure: A bathyal group at <3000 m in the New Hebrides and Kermadec trenches, an abyssal group (3039 – 4692 m) in the Kermadec Trench, an abyssal-hadal transition zone (AHTZ) group (Kermadec: 4707–6068 m, Mariana: 4506–6198 m, New Hebrides: 2578–6898 m, South Fiji Basin: 4074–4101 m), and a hadal group of endemic snailfish in the Kermadec and Mariana trenches (6750–7669 m and 6831–8143 m respectively). The abyssal and hadal groups were absent from the New Hebrides Trench. Depth was the single factor that best explained the biological variation between samples (16%), the addition of temperature and average surface primary production for the previous year increased this to 36% of variation. The absence of the abyssal group from the New Hebrides Trench and South Fiji Basin was due to the absence of macrourids ( Coryphaenoides spp.), which defined the group. The macrourids may be energetically limited in these areas. In their absence the species of the AHTZ group appear released of competition with the macrourids and are found far shallower at these sites. The fish groups had distinct feeding strategies while attending the bait: The bathyal and abyssal groups were almost exclusively necrophagous, the AHTZ group comprised predatory and generalist feeders, while the hadal snailfishes were exclusively predators. With increasing depth, predation was found to increase while scavenging decreased. The data suggest scavenging fish fauna do not extend deeper than the hadal boundary. Highlights: Three Pacific hadal trench system's fish communities are systematically sampled. Differences in the fish fauna of hadal trenches and surrounding plain are identified. Scavenging feeding behaviour in fishes is lost deeper than ~7000 m. The interaction of temperature and primary production may inhibit fish scavengers. A predatory ophidiid fish community may be more common globally than thought.